Cost-Efficiency Analysis of a Regulated Public Service: the case of Regional Bus Services in Italy - Roberto Fazioli (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1992)
This paper represents an application of the so-called evaluative or performance-approach to the analysis of a regulated sector as public transport. The aim of this work is to provide more information to the debate on the privatization programmes. A translog cost function for a five- year panel is estimated and measures of economies of scale and density are derived. Indeed, from the derived cost-efficiency frontier evidence for scale inefficiency and overall cost inefficiency can be noted for 40 regional bus companies in Emilia Romagna. The estimation results allow for a discussion of inefficiency in terms of sub-optimal scale and density. Overall cost inefficiency is estimated by means of a frontier cost function. The findings emphasize strong evidence for merger policies because of too little size of actual operators and non significant difference in cost-efficiency between public and private enterprises operating in a strongly regulated sector.
Keywords: 330